Teaching online in higher education - Oana BADEA (Social Sciences and Education Research Review)
The importance of e-Learning lays in the economic development, both of the individual and of the society, as the economy worldwide nowadays requires an educated, highly skilled and technologically literate labor force. There is no question about the fact that E-learning has become more and more used and indispensable in large educational areas, starting from middle school to academic educational programs. The future will bring new discoveries in this field and, subsequently, teachers and students will have to adjust to a new educational era, mainly based on E-learning.